Ischemic Stroke and Myocarditis Revealing Behçet’s Disease in a Young Adult: Diagnostic Challenges and Therapeutic Perspectives - Muhammed, Obeidat Saleh; B, Abdallani; Z, Amine; A, Boucetta; M, Bouziane; M, Haboub; R, Habbal (Journal of Cardiology and Cardiovascular Medicine, 2025)
Introduction: Behçet’s disease is a rare, systemic, inflammatory condition that primarily affects young adults. It is characterized by a variety of clinical manifestations. However, neurological and cardiac presentations remain uncommon and often delayed in diagnosis. This disease can lead to severe complications, such as ischemic strokes and myocarditis, highlighting the systemic and complex nature of the condition. Case presentation: A 27-year-old patient was hospitalized after experiencing an ischemic stroke and myocarditis, which revealed Behçet’s disease. He had a history of oral and cutaneous ulcers, without a prior diagnosis of Behçet. Upon admission, brain imaging confirmed an ischemic stroke, and echocardiography and cardiac MRI showed acute myocarditis. Biological tests confirmed elevated systemic inflammation, which guided the treatment plan. The initial treatment included corticosteroids, immunosuppressors (azathioprine), and cardioprotective therapy. The patient showed significant clinical improvements, although mild deficits persist. Discussion: Myocarditis in Behçet’s disease is a rare but severe manifestation resulting from inflammation of the heart walls, often associated with other systemic vascular involvement. Although less common than oral or cutaneous ulcers, myocarditis can lead to acute heart dysfunction and even heart failure if not treated promptly. It is generally caused by an excessive inflammatory response, often associated with immune system activation, which affects the coronary circulation and damages the cardiac muscle. Treatment for myocarditis in this context relies on high-dose corticosteroids to control inflammation, followed by long-term immunosuppressive medications like azathioprine. While the initial treatment often leads to a rapid improvement in cardiac function, the risk of long-term complications, such as dilated cardiomyopathy or heart failure, remains high. Close follow-up is therefore essential to prevent these complications and optimize the long-term cardiac prognosis of patients with this rare disease. Conclusion: The progression of myocarditis in Behçet’s disease can be favorable if diagnosed and treated early, with significant improvement in cardiac function achieved through the use of corticosteroids and immunosuppressive therapy. However, the long-term prognosis remains uncertain due to the risk of chronic cardiac complications, such as dilated cardiomyopathy or heart failure.